E-Commerce Recommender For Usage Bandwidth Hotel - Sfenrianto Sfenrianto; Melva Hermayanty Saragih; Bayu Nugraha (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The customer interest is often affected the promotions or product offered it his/her access. The aim of this research is to evaluate the recommendation system, as a promotion model or product offered, on e-commerce to the customer interest. This research focuses on e-commerce which offers the bandwidth internet for a hotel. Firstly, prototype of e-commerce which has recommendation system is built. Then, the eCommerce is evaluated by value creation of an eCommerce. There are four factors value creation, efficiency, lock-in, complementary and novelty based on R. Amit’s and Zott theory. After conducting the evaluation, two factors, efficiency and complementary, are significant to the value creation for eCommerce recommendation, yet the other factors, lock-in and novelty are not significant. This research also confirms that the number of subscribers’ eCommerce increases until 45.06% with using the recommendation than without recommendation.